Willful defiance: the movement to dismantle the school-to-prison pipeline - Warren, Mark R. (Oxford University Press, 2022)
Introduction: Confronting the School-to-Prison Pipeline: Journeys to Racial Justice Organizing -- The School-to-Prison Pipeline: Criminalization as Racial Domination and Control -- "Nationalizing local struggles:" Community Organizing and Social Justice Movements -- "There is no national without the local:" Building a National Movement Grounded in Local Organizing -- The Prevention of Schoolhouse to Jailhouse: Intergenerational Community Organizing in Mississippi -- Challenging Criminalization in Los Angeles: Building a Broad and Deep Movement to End the School to-Prison Pipeline -- From the Local to the State: Youth-led Organizing in Chicago -- The Movement Spreads: Organizing in Small Cities, Suburbs and the South -- The Movement Expands: Police-Free Schools, Black Girls Matter and restorative Justice -- Conclusion: Organizing and Movement-Building for Racial and Educational justice.